FORMULASI SEDIAAN HANDWASH EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Amanda, Yusi Lusiana; Nawangsari, Desy; Setianingsih, Siti (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Hands are a medium that can spread bacteria, this spread can be prevented by washing hands. Synthetic antibacterial ingredients such as triclosan in soap can damage the skin's normal flora. Starfruit leaves (Averrhoa bilimbi L.) are known to contain flavonoids, tannins, saponins and alkaloids. The aim of this research is to determine the physical properties and stability of handwash from the ethanol extract of starfruit leaves (Averrhoa bilimbi L.). This research uses experimental methods in making handwash with variations in the concentration of starfruit extract ethanol FI (10%), FII (12.5%) , and FIII (15%), the dosage for which physical properties were evaluated included organoleptic, homogeneity, pH, viscosity and foam height and stability tests were carried out using the cycling test method. Research shows that handwash preparations of ethanol extract of starfruit leaves have criteria according to soap standards set by SNI. The handwash preparation is homogeneous and the addition of the extract causes the preparation to be light brown in color, pH 8.2-9.7; viscosity 1,928-10,094 cPs; and foam height 1.53-1.93 cm. Has stable handwash preparation properties seen from the sig value. 2 tails > 0.05. Thus, the ethanol extract handwash from starfruit leaves has physical properties that comply with SNI including organoleptic, homogeneity, pH, viscosity and high foam and has stable properties.